Asymmetric information in secondary insurance markets: Evidence from the life settlements market. Issue 3 (17th July 2020) - Bauer, Daniel; Russ, Jochen; Zhu, Nan
Abstract : We use data from a large US life expectancy provider to test for asymmetric information in the secondary life insurance—or life settlements —market. We compare realized lifetimes for a subsample of settled policies relative to all (settled and nonsettled) policies, and find a positive settlement‐survival correlation indicating the existence of informational asymmetry between policyholders and investors. Estimates of the "excess hazard" associated with settling show the effect is temporary and wears off over approximately 8 years. This indicates individuals in our sample possess private information with regards to their near‐term survival prospects and make use of it, which has economic consequences for this market and beyond.